Cerebral venous thrombosis: A case series and a neuroimaging review of the literature. (December 2018) - Diacinti, Davide; Cartocci, Gaia; Colonnese, Claudio
Highlights: Imaging techniques have an important role in the diagnosis of cerebral venous thrombosis. GRE MRI sequences are useful in detecting CVT and during follow-up. MRI is important in follow-up when a diagnosis of cerebral venous thrombosis is doubtful. Cooperation between radiologists and neurologists is important to make diagnosis of cerebral venous thrombosis. Abstract: Cerebral venous thrombosis (CVT) is a rare condition, difficult to diagnose because of its non specific clinical symptoms. In some cases CVT can mimic other conditions as subarachnoid hemorrhage, ischemia or tumor and for these reasons diagnosis is delayed or missed. CT, DSA and MRI findings help to obtain an early diagnosis and to distinguish it from other diseases. Our cases involved four patients with no signs or symptoms suspected for CVT and without risk factors associated to this disease; furthermore some early imaging findings observed in these patients could mimic other diseases. The aim of presenting these cases is to underline the importance of some findings at imaging techniques in obtaining an early diagnosis of CVT; in particular we describe the usefulness of MRI with gradient echo sequences (GRE) in detecting the venous thrombus, suggesting that GRE sequences should be included in the MRI protocol when a CVT is suspected. We also underline the role of radiologists in helping neurologists to make an early diagnosis of CVT or when in doubt to encourage further investigations in order to begin the anticoagulation therapy as soon as possible avoiding the onset of complications as permanent parenchymal damage, cerebral hemorrhage and venous infarction.